PERAN FILSAFAT ILMU DALAM MEMBANGUN DASAR PEMIKIRAN KRITIS BERBASIS KEARIFAN LOKAL BUDAYA KERINCI (KENDURI SKO) PADA SISWA SEKOLAH DASAR - Silvia Meirisa (EDU RESEARCH, 2024)
This article discusses the role of the philosophy of science in building a foundation for critical thinking based on local wisdom of the Kerinci culture, particularly in the tradition of kenduri sko. The aim of this research is to explore and integrate the local wisdom values present in the Kerinci culture into the development of critical thinking skills in elementary school students. This study employs a literature review approach to analyze various references on the philosophy of science, critical thinking, and local wisdom. The findings indicate that utilizing local wisdom in the learning process can enrich students' perspectives, enhance their critical thinking abilities, and strengthen their cultural identity. This article is expected to contribute to the development of education based on local wisdom and improve the quality of elementary school learning.